Gypsum application in lowlands: soil chemical alterations and response of irrigated rice and soybean - Ghisleni, Gian (2020)
Studies that evaluate the crop responses to the soil modifications intermediated by gypsumapplication are relatively abundant, but most of them are performed in highlands. Such studies are still scarce in lowlands. The objective of our study was to evaluate soil acidity and phosphorus (P) and potassium (K) availability, as well as crop (irrigated rice and soybean) yields, as a function of different rates of gypsum application in lowland. The experiments were conducted in a Planosol (Triunfo, Rio Grande do Sul, Brazil). The treatments consisted of six gypsum rates (0.00, 0.25, 0.50, 1.00, 2.00 and 4.00 t ha-1) and the experimental design was in randomized blocks with four replications. The soil was sampled after crop harvests, in the 0–5, 5–10, 10–20 and 20–40 cm layers. The soil pH (in water), the potential acidity (H+Al) and the available P (Mehlich 1) were not affected by gypsum application. After the irrigated rice cropping and in the soil layer of 0–5 cm, the available K (Mehlich 1) contents was impacted by the gypsum application, with increase in content for rates up to 1.00 t ha-1 and decrease in content for higher rates (2.00 and 4.00 t ha-1). After the soybean cropping, the available K content was not affected by gypsum application. The gypsum application did not impact irrigated rice and soybean yields in the evaluated season, which did not present water deficit.